2016
DOI: 10.1186/s12889-016-2908-1
|View full text |Cite
|
Sign up to set email alerts
|

Do work-related factors contribute to differences in doctor-certified sick leave? A prospective study comparing women in health and social occupations with women in the general working population

Abstract: BackgroundDoctor –certified sick leave is prevalent in the health and social sector. We examined whether the higher risk of doctor-certified sick leave in women in health and social occupations compared to women in other occupations was explained by particular work-related psychosocial and mechanical risk factors.MethodsA randomly drawn cohort aged 18–69 years from the general population in Norway was surveyed in 2009 (n = 12,255, response at baseline = 60.9 %), and was followed up in the national registry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 23 publications
3
54
0
Order By: Relevance
“…12 13 Findings from Norway indicated that the higher risk of sickness absence among those employed in health and social occupations was largely explained by their unfavourable psychosocial and physical working conditions. 13 A Finnish study also showed that employees in the combined sector of education, health and social work had poorer health in terms of a higher risk of hospitalisation compared with those in other sectors. This applied to various disease groups, including musculoskeletal diseases and mental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 13 Findings from Norway indicated that the higher risk of sickness absence among those employed in health and social occupations was largely explained by their unfavourable psychosocial and physical working conditions. 13 A Finnish study also showed that employees in the combined sector of education, health and social work had poorer health in terms of a higher risk of hospitalisation compared with those in other sectors. This applied to various disease groups, including musculoskeletal diseases and mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…12 Accordingly, a Norwegian study indicated that the risk of long-term sickness absence was higher among women employed in health and social occupations than among the general female-employed population. 13 There may also be an important interplay between occupational class and industrial sector; even within a particular occupational class, the types of jobs may vary considerably between different sectors. Previous population-based findings from Denmark 12 and Sweden 14 have shown large differences in long-term sickness absence between particular occupational groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, if part-time employees bear the burden of their illness during their non-working hours, it might highlight an inequality of involuntary part-time employment. Finally, several studies on sickness absence include work hours as a control variable (Aagestad, Tyssen, & Sterud, 2016;Bernstrøm, 2013;Böckerman & Laukkanen, 2010a), sometimes without showing or commenting on the relationship between the two. Not knowing how or why work hours influence sickness absence can obscure study results.…”
mentioning
confidence: 99%
“…While physical work conditions are the most likely explanations for the socioeconomic gradient in LTSA (Christensen et al 2008;Löve et al 2013), also psychosocial factors are pertinent (Melchior et al 2005;Niedhammer et al 2008). Similarly, certain physical and psychosocial hazards have also been linked to heightened risk of LTSA for caring work (Aagestad et al 2016) and researchers have particularly emphasized the emotional demands as straining (Indregard et al 2017;Rugulies et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The argument for a distinction between caring and noncaring professionals is that the handling of clients with personal needs implies a heightened risk of LTSA. Workers in health care and social services have a high risk (Lund et al 2007), and a recent study found that awkward lifting, threats of violence, actual violence, and emotional demands explained a substantial part of the difference in the risk of LTSA for women in these services compared with women in the general working population (Aagestad et al 2016).…”
Section: Previous Research On Predictors Of Ltsa and Hypothesesmentioning
confidence: 99%